RELIGIOSITY AND HALAL LITERACY AS DETERMINANTS OF CONSUMER DECISION-MAKING IN PURCHASING HALAL FOOD VIA ONLINE PLATFORMS - Nurheti, Nurheti; Wahyudi, Dedi (Jurnal TAM (Technology Acceptance Model), 2025)
This study aims to analyze the influence of religiosity and halal literacy on consumer decisions in purchasing halal food through online platforms. This research applies a quantitative approach using a correlational method. The population consists of millennial generation high school students in Pringsewu Regency, with a sample of 150 respondents selected randomly. The research instrument was a questionnaire that had been tested for validity and reliability. The results of the multiple linear regression test indicate that religiosity and halal literacy have a positive and significant influence on online halal food purchasing decisions, both partially and simultaneously. The coefficient of determination (R²) is 0.539, indicating that 53.9% of purchasing decisions are explained by religiosity and halal literacy, while the remaining percentage is influenced by other factors. These findings emphasize the importance of halal education and the strengthening of religious values in shaping halal consumption behavior among the younger generation.